SMART SPRAYER DISINSFEKTAN BERBASIS MIKROKONTROLER ATMEGA328 - Zulkarnaen Zulkarnaen (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2020)
During the pandemic covid 19 we are experiencing at this time, various technological innovations are created as the first step in breaking the chain of corona virus. One way that can be implemented in breaking the covid pandemic chain of 19, especially in public areas is by spraying a disinfectant liquid that can be done continuously. Optimization of spraying disinfectant liquid can be done by utilizing technology that is able to work automatically. This research makes a disinfectant sprayer chamber as a technological innovation. Automation of disinfectant sprayers can be done by utilizing the ATemega328 microcontroller as an automatic machine to activate the sprayer pump based on the detection of objects that are around it with the help of an ultrasonic sensor. Determination of the distance reading of the object greatly determines the performance of the ultrasonic sensor in providing input to the microcontroller. The smart sprayer system is capable of activating a 12Volt DC pump with a voltage of 5 amperes. This smart sprayer disinfectant control system can be applied to the gate or hallway at the center of the crowd.